CFD Simulation of Building Double Skin Façade on Building’s Thermal Comfort and Energy Saving - Koo , Victor Zhao En (IRC, 2018)
To reduce the global energy consumption means the emission of greenhouse gases will be reduced. One of the high energy consumption sector is building, especially the cooling facilities include refrigerator and air conditioner. Previous researches studied that implementation of double skin façade (DSF) able to reduce the cooling load of the building by reducing the amount of thermal energy from solar irradiance transfer into the building. However, the design of the DSF inner surface configuration of the façade had not been studied. It is known that the higher surface area gives higher heat transfer rate, which will eventually affect the cavity temperature and velocity, and increase the stack effect in the cavity. At the same time, when the cavity temperature will increase, that might give the chance for the thermal energy to travel to the building’s wall. Hence, this project will find out the effect of the inner surface configuration design of DSF to the inner wall surface temperature to provide better thermal comfort and higher energy saving. Computational Fluid Dynamics (CFD) – fluent simulator will be used in this research for the implementation of four different possible DSF inner surface configurations design with the evaluation of fins’ height to cavity thickness ratio for each design. Result of the building’s inner wall temperature for each simulation will be used to identify the most suitable DSF design with evaluation and justification via temperature and velocity of cavity air, and building’s inner wall surface temperature. The scope of the project will cover Ipoh, Malaysia climate, which is tropical country.